Mutations in the AP1S2 gene encoding the sigma 2 subunit of the adaptor protein 1 complex are associated with syndromic X-linked mental retardation with hydrocephalus and calcifications in basal ganglia. Issue 11 (6th July 2007) - Saillour, Y; Zanni, G; Des Portes, V; Heron, D; Guibaud, L; Iba-Zizen, M T; Pedespan, J L; Poirier, K; Castelnau, L; Julien, C; Franconnet, C; Bonthron, D; et al.
Abstract : Fried syndrome, first described in 1972, is a rare X-linked mental retardation that has been mapped by linkage to Xp22. Clinical characteristics include mental retardation, mild facial dysmorphism, calcifications of basal ganglia and hydrocephalus. A large four-generation family in which the affected males have striking clinical features of Fried syndrome were investigated for linkage to X-chromosome markers; the results showed that the gene for this condition lies within the interval DXS7109–DXS7593 in Xp22.2. In total, 60 candidate genes located in this region, including AP1S2, which was recently shown to be involved in mental retardation, were screened for mutations. A mutation in the third intron of AP1S2 was found in all affected male subjects in this large French family. The mutation resulted in skipping of exon 3, predicting a protein with three novel amino-acids and with termination at codon 64. In addition, the first known large Scottish family affected by Fried syndrome was reinvestigated, and a new nonsense mutation, p.Gln66X, was found in exon 3. Using CT, both affected patients from the French family who were analysed had marked calcifications of the basal ganglia, as previously observed in the first Scottish family, suggesting that the presence of distinctive basal ganglia calcification is an essential parameter to recognise this syndromic disorder. It may be possible to use this feature to identify families with X-linked mental retardation that should be screened for mutations in AP1S2 .